2014
DOI: 10.5312/wjo.v5.i3.319
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines: Biomarkers for osteoarthritis?

Abstract: Osteoarthritis (OA) is one of the most common degenerative joint diseases in aging population. Obesity is an important risk factor for initiation and progression of OA. It is accepted that excess body weight may lead to cartilage degeneration by increasing the mechanical forces across weight-bearing joints. However, emerging data suggest that additional metabolic factors released mainly by white adipose tissue may also be responsible for the high prevalence of OA among obese people. Adipocyte-derived molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 78 publications
2
87
0
Order By: Relevance
“…Obesity has long been considered as a risk factor for OA initiation as well as the disease progression. Particularly, adipokines might be a potential biomarker for OA progression and classify the disease severity [16]. However, Harvey et al [17] explored the association of leg-length inequality with knee OA, whereby the result for progressive knee OA was less clear compared with incident knee OA.…”
Section: Introductionmentioning
confidence: 98%
“…Obesity has long been considered as a risk factor for OA initiation as well as the disease progression. Particularly, adipokines might be a potential biomarker for OA progression and classify the disease severity [16]. However, Harvey et al [17] explored the association of leg-length inequality with knee OA, whereby the result for progressive knee OA was less clear compared with incident knee OA.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, adiponectin levels in OA synovial fluid was correlated with aggrecan degradation. 20 Hence from above it is clearly indicated that adiponectin plays crucial role in providing inflammatory environment in OA. Franchin et al, produced similar results where authors have shown link between adiponectin and cartilage degradation.…”
Section: Role Of Adiponectinmentioning
confidence: 99%
“…Researchers have started believing that adipokines plays a crucial role in homeostasis of cartilage and bone. 20 …”
Section: Role Of Adipokinesmentioning
confidence: 99%
See 2 more Smart Citations